A BEME systematic review of teaching interventions to equip medical students and residents in early recognition and prompt escalation of acute clinical deteriorations: BEME Guide No. 62. (2nd July 2020) - Ashokka, Balakrishnan; Dong, Chaoyan; Law, Lawrence Siu-Chun; Liaw, Sok Ying; Chen, Fun Gee; Samarasekera, Dujeepa D.
Abstract: Background: Current educational interventions and teaching for acute deteriorations seem to address acute care learning in discreet segments. Technology enhanced and team training methodologies are in vogue though well studied in the nursing profession, teaching avenues for junior 'doctors in training' seem to be a lacuna. Aims: The BEME systematic review was designed to (1) appraise the existing published evidence on educational interventions that are intended for 'doctors in training' to teach early recognition and prompt escalation in acute clinical deteriorations (2) to synthesise evidence & to evaluate educational effectiveness. Methodology: The method applied was a descriptive, justification & clarification review. Databases searched included PubMed, PsycINFO, Science Direct and Scopus for original research and grey literature with no restrictions to year or language. Abstract review, full text decisions and data extraction were completed by two primary coders with final consensus by a third reviewer. Results: 5592 titles and abstracts were chosen after removal of 905 duplications. After exclusion of 5555 studies, 37 full text articles were chosen for coding. 22 studies met final criteria of educational effectiveness, relevance to acute care. Educational platforms varied from didactics to blended learning approaches, small group teaching sessions, simulations, live & cadaveric tissue training, virtual environments and insitu team-based training. Translational outcomes with reduction in long term (up to 3–6 years) morbidity & mortality with financial savings were reported by 18% (4/22) studies. Interprofessional training were reported in 41% (9/22) of studies. Recent evidence demonstrated effectiveness of virtual environment and mobile game-based learning. Conclusions: There were significant improvements in teaching initiatives with focus on observable behaviours and translational real patient outcomes. Serious game-based learning and virtual multi-user collaborative environments might enhance individual learners' cognitive deliberate practice. Acute care learning continuum with programmatic acute care portfolios could be a promise of the future.